2003
DOI: 10.1002/ajmg.b.20132
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for linkage between regulatory enzymes in glycolysis and schizophrenia in a multiplex sample

Abstract: Observations of impaired glucose regulation in schizophrenia are long-standing, although their pathological and etiological significance is uncertain. One approach to the issue that minimizes environmental variables (e.g., medication and diet) is to determine whether genes related to glucose regulation show genetic linkage to schizophrenia. We examined the potential role of glucose metabolism in schizophrenia through a genome scan of affection status in schizophrenia and an empirical method for deriving P-valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 38 publications
1
36
0
Order By: Relevance
“…Stone et al (2004) identified positive associations between schizophrenia and several enzymes involved in glycolysis, including 6-phosphofructo-2-kinase/fructose-2, 6-biphophatase 2, hexokinase 3, and pyruvate kinase 3. Similarly, olanzapine treatment of rats caused significant alterations in several key glycolytic enzymes, such as increases in muscle glycogen phosphorylase and in RBC and liver pyruvate kinase (which also showed a near significant increase based on our QPCR results; Table 2) and a decrease in sucrase-isomaltase (Tables 1, 3).…”
Section: Chronic Olanzapine Treatment Sh Fatemi Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…Stone et al (2004) identified positive associations between schizophrenia and several enzymes involved in glycolysis, including 6-phosphofructo-2-kinase/fructose-2, 6-biphophatase 2, hexokinase 3, and pyruvate kinase 3. Similarly, olanzapine treatment of rats caused significant alterations in several key glycolytic enzymes, such as increases in muscle glycogen phosphorylase and in RBC and liver pyruvate kinase (which also showed a near significant increase based on our QPCR results; Table 2) and a decrease in sucrase-isomaltase (Tables 1, 3).…”
Section: Chronic Olanzapine Treatment Sh Fatemi Et Almentioning
confidence: 99%
“…Impairment of glycolytic pathways has been investigated in schizophrenia (Stone et al, 2004). Stone et al (2004) identified positive associations between schizophrenia and several enzymes involved in glycolysis, including 6-phosphofructo-2-kinase/fructose-2, 6-biphophatase 2, hexokinase 3, and pyruvate kinase 3.…”
Section: Chronic Olanzapine Treatment Sh Fatemi Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…These changes were not attributable to antipsychotic treatment, which may have a restorative effect (11). Further, a genetic study demonstrated evidence for linkage between enzymes that control glycolysis, such as 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase 2 (PFKFB2), hexokinase 3 (HXK3), and pyruvate kinase 3 (PK3),suggesting that genetic risk for this illness includes bioenergetic substrates (14). …”
Section: Introductionmentioning
confidence: 99%
“…The basic mechanisms behind these metabolic irregularities have not been fully elucidated, but it appears that antipsychotic medications could play an important role (Newcomer, 2005). Moreover, high rates of obesity and type II diabetes mellitus, observed in drug-naive/free patients (Mukherjee et al, 1996;Allison et al, 1999a;Thakore et al, 2002;Ryan et al, 2003Ryan et al, , 2004 before Kohen, 2004) and after the advent of antipsychotics and in nonschizophrenic blood relatives (Dynes, 1969;Mukherjee et al, 1989;Cheta et al, 1990;Martins et al, 2001;Lamberti et al, 2004), were potentially attributed to genetic factors (Stone et al, 2004), illness neurobiology (Thakore, 2005) and to unhealthy lifestyle (Brown et al, 1999). The interpretability of the preneuroleptic era data (reviewed in Kohen, 2004) is, however, limited by flaws in epidemiological methodology including lack of evaluation of and adjustments for adiposity, lifestyle, and anthropometric measures together with inconsistent diagnostic criteria for schizophrenia and glucose/insulin abnormalities Newcomer, 2005).…”
mentioning
confidence: 99%